An Evaluation of Construction and Demolition (C&D) Waste as a Road Construction Material - Jitsangiam, Peerapong; Siripun, Komsun; Nikraz, Hamid (Khon Kaen University, 2012)
A high quality of natural aggregates is demanded for use in pavement construction and the sources, which are becoming scarce. The search for alternative materials to minimize the utilization of natural aggregates and provide a significant substitute has led to the utilization of Construction and Demolition (C&D) waste. This paper describes a preliminary examination of the engineering issues relating to the utilization of C&D waste as a base course material for Western Australia roads. A series of laboratory tests were performed during which Repeated Load Triaxial (RLT) tests were conducted to determinethe resilient modulus and permanent deformation characteristics of C&D waste and the commonly used base course material, Crushed Rock Base (CRB), as a reference material. A comparison of test results of both materials then was made. CIRCLY, a computer program based on the multi-layer elastic theory was used in the mechanistic approach of pavement design and analysis to determine the performance of a typical pavement model using C&D as a base course layer. Based on the study’s findings, C&D waste should be considered an adequate substitute for traditional aggregate in Western Australia road construction.